2007
DOI: 10.1101/sqb.2007.72.034
|View full text |Cite
|
Sign up to set email alerts
|

A PER/TIM/DBT Interval Timer forDrosophila's Circadian Clock

Abstract: Circadian rhythms in Drosophila are supported by a negative feedback loop, in which PERIOD (PER) and Timeless (TIM) shut down their own transcription as they translocate once a day from the cytoplasm of clock-containing cells to the nucleus. Period length is partially determined by an interval of cytoplasmic retention of the TIM and PER proteins. To study this process, we examined PER/TIM/Doubletime (DBT) physical interactions and nuclear translocation by imaging individual cultured Drosophila cells. Using liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
(71 reference statements)
2
22
0
Order By: Relevance
“…More recent in vitro experiments using fluorescently labeled clock proteins in individual S2 cells demonstrated that a substantial fraction of DBT localize to the nucleus when over-expressed alone or with TIM (15), consistent with in vivo studies that indicate nuclear localization of DBT in per 01 and per 0 fly heads (8,16). However, when coexpressed with PER, the study showed that DBT is mostly cytoplasmic and the PER-DBT interaction can lead to gradual turnover of PER (15). This preliminary PER-DBT study established that the proteins interact in S2 cells but it did not fully explore the kinetics of the ensuing degradation process.…”
Section: Robust Circadian Oscillations Of the Proteins Period (Per)supporting
confidence: 63%
“…More recent in vitro experiments using fluorescently labeled clock proteins in individual S2 cells demonstrated that a substantial fraction of DBT localize to the nucleus when over-expressed alone or with TIM (15), consistent with in vivo studies that indicate nuclear localization of DBT in per 01 and per 0 fly heads (8,16). However, when coexpressed with PER, the study showed that DBT is mostly cytoplasmic and the PER-DBT interaction can lead to gradual turnover of PER (15). This preliminary PER-DBT study established that the proteins interact in S2 cells but it did not fully explore the kinetics of the ensuing degradation process.…”
Section: Robust Circadian Oscillations Of the Proteins Period (Per)supporting
confidence: 63%
“…Nuclear translocation is a particularly promising avenue for future research. A great deal about the biochemistry of nuclear translocation has been discovered in the last decade (19), and much of this knowledge can be leveraged into experiments on temperature compensation. Additionally, the multifarious network of reversible phosphorylations known to regulate nuclear translocation of the PER-TIM dimer bears an intriguing resemblance to models of temperature compensation in the literature (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…ref. 19). The advent of fluorescent protein-tagging experiments on the circadian clock in Neurospora (74,75), as well as reporter experiments in mammalian fibroblasts (76), will allow observation of the effect of temperature changes on multiple subprocesses of the circadian clock in a single experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where the clock proteins are localized within the cell and how this localization may change and contribute to clock function have not been previously addressed. In eukaryotic systems subcellular localization is an important feature of timekeeping and several clock components display rhythms of nuclear localization [25, 26] and even rhythmic formation of sub-nuclear structures [27]. …”
Section: Introductionmentioning
confidence: 99%